Proteomic analysis identified potential age‐associated prognostic biomarkers in pneumonia‐derived paediatric sepsis. Issue 3 (4th December 2021) - Luo, Ting; Yan, Haipeng; Li, Xun; Deng, Youcai; Huang, Jiaotian; Li, Liping; Xiao, Zhenghui; Lu, Xiulan
Abstract: Purpose: Our aim was to investigate the age‐associated plasma protein profiles in pneumonia‐derived sepsis between infants and toddlers and identify potential age‐adapted prognostic markers for poor outcome of pneumonia‐derived pediatric sepsis. Experimental Design: A nested case‐control study strategy was applied. The plasma proteomes of pneumonia‐derived pediatric septic patients with different outcomes between infants and toddlers were respectively analysed compared to their age‐matched controls. Results: Compared to toddlers, pneumonia‐derived sepsis in infants was characterized by increased upregulation of protein processing in the ER, proteasome and antigen processing and presentation; and reduced downregulation in complement and coagulation cascades and cholesterol metabolism. Among them, the pentose phosphate pathway as well as the complement and coagulation cascades were possibly associated with poor outcome of pneumonia‐derived sepsis. Furthermore, we confirmed that HP, THBS1, and SAA1/2 were potential prognostic markers for poor outcome of pneumonia‐derived sepsis in infant patient groups. Conclusions and Clinical Relevance: Age‐associated plasma protein profiles of pneumonia‐derived pediatric septic patients provided potential age‐adapted biomarkers for a more precise prognosis of poor outcome in pneumonia‐derived pediatric sepsis and helped to improve the survival of septic children.